Real‐Time Internal Steam Pop Detection during Radiofrequency Ablation with a Radiofrequency Ablation Needle Integrated with a Temperature and Pressure Sensor: Preclinical and Clinical Pilot Tests. Issue 19 (5th August 2021) - Park, Jaeho; Cha, Dong Ik; Jeong, Yongrok; Park, Hayan; Lee, Jinwoo; Kang, Tae Wook; Lim, Hyo Keun; Park, Inkyu
Abstract: A radiofrequency ablation (RFA) needle integrated with a temperature sensor (T‐sensor) and pressure sensor (P‐sensor) is designed and utilized for real‐time internal steam pop monitoring during RFA. The characteristics of the sensor‐integrated RFA needle (sRFA‐needle) are investigated quantitatively using a pressure chamber system, and the feasibility and usability of the needle in preclinical and clinical trials is demonstrated. The sharp changes in the temperature and normalized pressure sensor signals induced by the abrupt release of hot and high‐pressure steam can be clearly monitored during the steam pop phenomena. The basic mechanism of the preliminary steam pop is hypothesized and verified using in situ ultrasound imaging data and computational analysis data of the RFA procedure. Moreover, the usability of the system in clinical trials is investigated, and the steam pop phenomena during the RFA procedure are detected using T‐sensor and P‐sensor. The results confirm that the sensor integration on the medical needle can provide critical data for safer and more effective medical practices. Abstract : A radiofrequency ablation (RFA) needle integrated with a flexible thin‐film type temperature and a pressure sensor is reported and its clinical applications toward real‐time detection of internal steam pop and monitoring of environmental change in the ablation zone are studied. The study is performed in a pre‐clinical trial (animal study) and clinical trial (human study) to verify their usefulness in an in‐vivo environment.